Attentive Observation Is Essential for the Misattribution of Agency to Self-Performance - Kashihara, Shiho; Kanayama, Noriaki; Miyatani, Makoto; Nakao, Takashi (Frontiers in Psychology, 2017)
Recent studies have repeatedly demonstrated self-other confusion in action memory by observing another’s actions (i.e., observation inflation). We investigated the attentional effect to the action itself on self-other confusion. Fifty-four participants first performed and read actions (Phase 1); then, they observed the action video that showed another’s actions, some of which they had not performed earlier. In the observation phase, they were required to focus on either the actor’s performance (i.e., attentive observation condition) or irrelevant objects, which were presented in the background (i.e., inattentive observation condition) to modulate their attention. Around two weeks later, participants took a surprise source-memory test that asked them to judge whether they “performed,” “read,” or “not presented” the action in Phase 1. We only found observation inflation in the attentive condition, which contradicted the notions from other false memory studies that showed that attention to the target stimuli reduced false memory in general. We discussed the observation inflation mechanism from the perspective of the “like me” system, including the mirror neuron system, self-ownership, and self-agency.